The Influence of Service Quality, Customer Review, and Convenience on The Decision to Donate on Lazismu DIY - Sutrisno (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to measure the relationship between service quality, customer reviews and ease of making donation decisions at Lazismu, Special Region of Yogyakarta. This study uses a quantitative approach with a data collection technique using a questionnaire with a total of 250 respondents. The results of the questionnaire were collected and analyzed using the SmartPLS application version 3.29. The results obtained indicate that the variables of service quality, customer reviews and convenience have a positive and significant influence on the decision to donate to the Yogyakarta community at Lazismu DIY. Service quality is categorized as good in relation to welcoming donors, donation services, intense communication, smiles and greetings, which are in accordance with the expectations of donors who donate to Lazismu DIY. Good service that meets the quality and expectations of donors will increase the satisfaction and loyalty of donors in general and can encourage sustainable donation decisions.